Optimization of stormwater purification: coolant temperature and operation time - Salim, Siti Aquilah (2019)
Shortage and lack of sources of clean water is a big issue nowadays. This problem happens because of the increment of population. New sources of water need to be discovered. Therefore, the sources of water must be explored in order to get continuously supply of pure water. One of the ways to get pure water is by purifying the storm water. The method used to purify storm water in this research is by using progressive freeze concentration, PFC. This process produces ice crystal block that contain pure water through cooling process. This method has been chosen because it is a simple process that leads to low cost compared to other method. However, in order to obtain the high quality and quantity of pure water, it is important to determine the optimum condition for the system. Therefore, this research aims to investigate the optimum condition for coolant temperature and operation time. The objectives of this research are to investigate the optimum condition for coolant temperature and operation time for storm water purification through PFC system and to study interaction between coolant temperature and operation time. This research was conducted by using simulated stormwater. The simulated stormwater was performed by using zinc chloride and water. Besides that, the efficiency of the system was determined by using effective partition constant (K) and concentration efficiency (Eff). To run this experiment, the range of coolant temperature is between -6°C to - 10°C while for operation time is between 10 minutes to 50 minutes. The optimization for this system was analysed by using research surface methodology (RSM) and the type of chemical composition that was investigated is composition of zinc. From this experiment, the result shows that the R2 for generated model using Statistica Software is 0.97. This shows that the regression model is best fit to the data. For optimum condition, the result shows that at -8.9oC for coolant temperature and 41 minutes for operation time is the best optimum condition in order to get the best quality of pure water. The best value of K and Eff resulting from this optimum condition are 0.1096 and 89.0235, respectively.